2007
DOI: 10.1097/mnm.0b013e3282742035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EMDR psychotherapy on 99mTc-HMPAO distribution in occupation-related post-traumatic stress disorder

Abstract: Significant 99mTc-HMPAO uptake regional differences were found, mainly in the peri-limbic cortex, between PTSD patients and controls exposed to trauma but not developing PTSD. Tracer uptake differences between responders and patients not responding to EMDR were found after treatment suggesting a trend towards normalization of tracer distribution after successful therapy. These findings in occupational related PTSD are consistent with previously described effects of psychotherapy on anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 34 publications
3
63
0
14
Order By: Relevance
“…Previous research showed that compared with non-EMDR therapy, EMDR therapy exerts a greater effect in reducing psychophysiological disturbances that may aid in processing negative memories [33]. Furthermore, the brain image study determined that activities in the frontal, parietooccipital, and visual cortices and hippocampus increased after the intervention of EMDR [38]. These areas moderate the experience of a real versus perceived threat.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research showed that compared with non-EMDR therapy, EMDR therapy exerts a greater effect in reducing psychophysiological disturbances that may aid in processing negative memories [33]. Furthermore, the brain image study determined that activities in the frontal, parietooccipital, and visual cortices and hippocampus increased after the intervention of EMDR [38]. These areas moderate the experience of a real versus perceived threat.…”
Section: Discussionmentioning
confidence: 94%
“…These areas moderate the experience of a real versus perceived threat. However, it indicates that after EMDR intervention, adolescents with PTSD may no longer be hypervigilant during processing traumatic memory [38]. Thus, it would help the victims to resume conversation with related story and symptoms [39].…”
Section: Discussionmentioning
confidence: 99%
“…72 In addition, the effects of eye movement desensitization and reprocessing therapy on CBF in a group of PTSD patients listening to a traumatic script showed that a significant tracer difference present before treatment in the uncus (BA 36) disappeared after treatment, while a significant difference appeared in the lateral temporal pole (BA 21). 73 Furthermore, in a group of 8 patients with PTSD, imaginal exposure and cognitive restructuring was associated with increased activation in the rostral anterior cingulate cortex, 74 and improvements in PTSD symptom severity were correlated with increased rostral anterior cingulate activation and decreased amygdala activation. The effects of brief eclectic therapy involving trauma imagery in civilian PTSD patients were associated with decreased CBF in the right middle frontal gyrus as determined by PET.…”
Section: Should Neuroimaging Studies Include Ptsd Patients Receiving mentioning
confidence: 99%
“…Because of issues arising with repeated measurements in neuroimaging (habituation and training effects) or the possibility of spontaneous recovery over the time, only the use of control groups, such as healthy controls groups and/or a waitlist control group, allows excluding possible confounds from the observed changes. Many of the discussed studies used a healthy control group (Baxter et al 1992;Nakatani et al 2003;Nakao et al 2005;Nabeyama et al 2008;Saxena et al 2009;Paquette et al 2003;Straube et al 2006;Schienle et al 2007Schienle et al , 2009Goosens et al 2007;Leutgeb et al 2009;Brody et al 2001b;Fu et al 2008;Dichter et al 2009Dichter et al , 2010Farrow et al 2005;Lindauer et al 2005Lindauer et al , 2008Pagani et al 2007) and some also a waitlist control group (Furmark et al 2002;Straube et al 2006;Schienle et al 2007;Leutgeb et al 2009;Lehto et al 2008;Lindauer et al 2005Lindauer et al , 2008.…”
Section: Discussionmentioning
confidence: 98%
“…Activation increased in the anterior cingulus. Pagani et al (2007) used a symptom provocation design to study the effect of the eye movement desensitisation and reprocessing technique (EMDR; Shapiro 1995), finding no significant changes in the patient group as a whole, but some evidence of normalisation of fronto-limbic activity in responders. This study, however, did not test the interaction of time and group directly.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%